Pengembangan Superkapasitor Bank dengan Kontroler ESP-32 Berbasis IoT sebagai Alat Penyimpan Energi - Djukarna Djukarna; Murni Murni (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2023)
The purpose of this study is to develop an electrical energy storage device using a supercapacitor that is equipped with a dynamic voltage balancing system and an IoT-based controller that can send data on the condition of the bank supercapacitor to users via a wireless network. This research is a type of research and product development with a 4D development model. The process of design, manufacture, and testing is carried out in the laboratory using a dummy voltage source. The data processed in the study are the total voltage of the supercapacitor bank, the maximum voltage of each individual supercapacitor in the supercapacitor bank, the strength of the current supplied to the supercapacitor and the time required for the charging and emptying of the supercapacitor. The instruments used to create bank supercapacitors are capacitors, resistors, ESP-32 controllers, Zener diodes, and voltage sources. The research data was obtained using the Arduino IDE application and then plotted into a graph. Data processing will result in the performance of the bank supercapacitor which includes the total capacity of the supercapacitor, the maximum current that can be supplied, and the most ideal conditions for the charging and discharging of the supercapacitor bank. The result of this study is the development of a supercapacitor bank as an energy storage tool that has been equipped with a dynamic voltage balancing system and an IoT-based controller that can send data on the condition of the supercapacitor bank to users via a wireless network. This supercapacitor bank can be used instead of batteries that can be used as a voltage charger on electric bicycles, power banks, and non-battery electrical energy stores.